2018
DOI: 10.1007/s00270-018-2029-6
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the Posterior Communicating Artery Contributes to the Clinical Outcome After Endovascular Treatment of Patients with MCA Occlusions

Abstract: The presence of an ipsilateral PComA is a predictor for excellent clinical outcome independently from the technical success of mechanical recanalization. This finding provides insights into the changes of circulation in patients suffering from an acute stroke and underlines the importance of collateralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Second, the rate of PComA patency may vary according to different parameters (setting of a large vessel occlusion, modality of assessment, definitions between absence, hypoplasia, and presence). 6,12,13 Therefore, it is possible that the important number of patients without a PComA is partly explained by our methodology (assessment on the first angiographic run, no computed tomography angiography adjudication). Third, no data regarding the hemodynamic management before EVT (notably in case of intravenous thrombolysis) and during the patient’s transfer was available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the rate of PComA patency may vary according to different parameters (setting of a large vessel occlusion, modality of assessment, definitions between absence, hypoplasia, and presence). 6,12,13 Therefore, it is possible that the important number of patients without a PComA is partly explained by our methodology (assessment on the first angiographic run, no computed tomography angiography adjudication). Third, no data regarding the hemodynamic management before EVT (notably in case of intravenous thrombolysis) and during the patient’s transfer was available.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is substantiated by a preliminary study that showed worse FO in patients treated with EVT that had no PComA. 6 Altogether, it is plausible that hypotension during EVT may have a varying effect on FO according to the patency of the PComA. We sought to evaluate this question in patients with an M1/M2 occlusion.…”
mentioning
confidence: 98%
“…Using magnetic resonance angiography (MRA) in 874 men and 990 women, Hindenes et al found 47 unique variations in the Circle of Willis, where the absence of the posterior communicating arteries is the most common variation ( 27 ). This is clinically relevant, as acute MCA occlusions in patients with a present ipsilateral posterior communicating artery are more likely to have favorable functional outcomes (i.e., modified Rankin score <2) after successful endovascular mechanical thrombectomy, compared to those without an ipsilateral posterior communicating artery ( 28 ). The recruitment of leptomeningeal collaterals is hypothesized to occur when the primary collaterals have failed to provide adequate blood flow to the ischemic regions ( 24 ), since leptomeningeal arteries are primarily observable in the later phases of ischemia ( 29 ).…”
Section: The Cerebral Collateral Circulation Systemmentioning
confidence: 99%